1998
DOI: 10.1136/bmj.316.7129.417
|View full text |Cite
|
Sign up to set email alerts
|

Risk of connective tissue disease and related disorders among women with breast implants: a nation-wide retrospective cohort study in Sweden

Abstract: Objective: To examine the relation between connective tissue disease and related conditions and breast implants. Design: Retrospective cohort study of all women in the Swedish national inpatient registry who underwent breast augmentation surgery with artificial implants during 1964-93, compared with women who underwent breast reduction surgery during the same period. Setting: Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(49 citation statements)
references
References 13 publications
0
48
0
1
Order By: Relevance
“…The diagnoses in the birth and inpatient registers are coded according to the International Classification of Diseases, Eighth Revision (ICD-8), through 1986, and according to the International Classification of Diseases,, from 1987 to the time of this report. The inpatient register provides nationwide coverage from 1986 onward, 17 but as no specific diagnostic code of anorexia nervosa was available before 1987 (ie, using ICD-8 codes), the study was restricted to include subjects with anorexia nervosa from 1987 through 1994.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnoses in the birth and inpatient registers are coded according to the International Classification of Diseases, Eighth Revision (ICD-8), through 1986, and according to the International Classification of Diseases,, from 1987 to the time of this report. The inpatient register provides nationwide coverage from 1986 onward, 17 but as no specific diagnostic code of anorexia nervosa was available before 1987 (ie, using ICD-8 codes), the study was restricted to include subjects with anorexia nervosa from 1987 through 1994.…”
Section: Study Populationmentioning
confidence: 99%
“…More than 99% of all births in Sweden are included in the birth register. 16 The Swedish Inpatient Register provides data on hospital discharges and diagnoses as classified by the treating physician, 17 and computerized information was available through 1994. The diagnoses in the birth and inpatient registers are coded according to the International Classification of Diseases, Eighth Revision (ICD-8), through 1986, and according to the International Classification of Diseases,, from 1987 to the time of this report.…”
Section: Study Populationmentioning
confidence: 99%
“…We did not find a relationship between increased SRSC complaints and ANA positivity or MRI changes in the silicone prostheses 1 year after SBI. While awaiting the results of the prospective study with a third measurement of SRSC-related complaints and ANA, we accept the conclusions from large retrospective cohort studies which could not find any risk of connective tissue disease in association with silicone prostheses [10,11,[28][29][30].…”
Section: Discussionmentioning
confidence: 92%
“…Concerns regarding auto-immune reaction against silicone implants remain among a small group of the population, despite the numerous studies showing safety of the new implants (22,23,25,27,28,41). Several clinical studies have shown no difference in the incidence of autoimmune diseases in mastectomy patients receiving silicone gel implants compared to patients who had reconstruction with autogenous tissue (45)(46)(47)(48)(49)(50)(51). Even meta-analysis research combining data from over 87,000 women has revealed no association between silicone breast implants and connective tissue diseases (52,53).…”
Section: Discussionmentioning
confidence: 99%